If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x) + -14x + 45 = 0 Multiply x * x x2 + -14x + 45 = 0 Reorder the terms: 45 + -14x + x2 = 0 Solving 45 + -14x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (5 + -1x)(9 + -1x) = 0Subproblem 1
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Subproblem 2
Set the factor '(9 + -1x)' equal to zero and attempt to solve: Simplifying 9 + -1x = 0 Solving 9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 0 + -9 -1x = 0 + -9 Combine like terms: 0 + -9 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9Solution
x = {5, 9}
| X=3x^2-5x-4 | | y-x=-10 | | 81x-8x^2=0 | | f(2)=4(2)+6 | | 21/2h-3/4=11/2 | | 7+1x=4 | | f(3)=4(3)+6 | | 1a^2-28a+192=0 | | 10D+5N=185 | | 5x+1=-2x+1 | | 8x-11x-22=-6 | | 3a-11/2=-51/4 | | 9ab^2= | | 2u-27=u | | 5+-2(x+-1)=2(3+4x)+7 | | 155/9 | | (2y-y)/(2x-5x) | | -4(3n-2)-n=11(n-1) | | 7p+22=10p-80 | | 3x+15=7x | | F(x)=3x^2-5x-4 | | -9(6+4k)=23 | | x+35=130 | | x-5x^2= | | d=mb+gaforb | | f(3)=4g+6 | | (3f+6)(2f-4)=0 | | -12n-n=11n-1 | | 5y-8=5y-8 | | F(x)=2x^2+6x+5 | | 7v-17=v+7 | | 6x+20=98 |